The association of lectin-like oxidized LDL receptor 1 (LOX-1) K167N and 3'UTR188CT polymorphisms with maternal plasma soluble LOX-1 levels and preeclampsia risk in Turkish population - Tuten, Abdullah; Aydemir, Birsen; Oncul, Mahmut; Kiziler, Ali Riza; Acikgoz, Abdullah Serdar; Korkmaz, Gulcan Guntas; Sozer, Volkan; Uzun, Hafize (SPRINGER HEIDELBERG, 2015)
To investigate the main effect of polymorphisms in genes involved in endothelial pathophysiological mechanisms, LOX-1 K167N and 3'UTR188CT single nucleotide polymorphisms (SNPs) in relation to preeclampsia (PE) risk and possible interactions between the gene polymorphisms and plasma oxLDL and soluble LOX-1 (sLOX-1) levels on PE in Turkish population. LOX-1 K167N and 3'UTR188CT polymorphisms were studied in 113 pregnant women with preeclampsia and 96 healthy pregnant women by the PCR-RFLP techniques. sLOX-1 and oxLDL levels were determined by enzyme-linked immunosorbent assay (ELISA) in all study subjects. Patients having LOX-1 3'UTR188CT (OR 3.55, 95 % CI 1.89-6.67, P = 0.001) or 3'UTR188CC (OR 3.04, 95 % CI 1.25-7.38, P = 0.012) genotype had a significantly higher risk of PE than those with 3'UTR188TT genotype. Also, patients having K167N KK (OR 2.73, 95 % CI 1.33-5.61, P = 0.005) genotype had a significantly higher risk of PE than those with K167N NN genotype. LOX-1 3'UTR188TT and LOX-1 K167N NN genotype carriers were associated with significantly increased serum sLOX-1 level (P = 0.001). We further investigated the potential combined effect of these polymorphic variants on risk of PE development. According to the combined genotype analysis of LOX-1 3'UTR188TT and K167N NN polymorphisms, sLOX-1 and oxLDL levels also showed significant differences between PE patients and controls with or without combined TT/NN genotype carriers. Our findings indicate that higher plasma sLOX-1 and oxLDL concentrations, and the LOX-1 3'UTR188C > T and LOX-1 K167N gene polymorphisms were significantly associated with risk of developing preeclampsia. Plasma sLOX-1 may be a potential therapeutic target in the treatment of preeclampsia.
Keywords: Preeclampsia; Soluble lectin-like oxidized LDL receptor-1; Lectin-like oxidized LDL receptor-1 gene polymorphism; Oxidized LDL; LOW-DENSITY-LIPOPROTEIN; CORONARY-ARTERY-DISEASE; ACUTE MYOCARDIAL-INFARCTION; OLR1 GENE; EXPRESSION; IDENTIFICATION; DYSFUNCTION; APOPTOSIS; SEVERITY; PLACENTA; Obstetrics & Gynecology